CVD risk in non-albuminuric chronic kidney disease in hypertensive, non-diabetic subjects: A post-hoc analysis from SPRINT - Sheng, Chang-Sheng; Wang, Dan; Yuan, Jiangzi; Cheng, Yi; Sun, Siming; Yang, Yulin; Miao, Ya; Wang, Weiming; Tian, Jingyan; Bloomgarden, Zachary T. (Frontiers in Cardiovascular Medicine, 2022)
Introduction The risks associated with non-albuminuric chronic kidney disease (CKD) have been investigated in diabetes mellitus but not in hypertensive patients. The objective of this study was to investigate the risks associated with non-albuminuric CKD in treated hypertensive patients in the Systolic Blood Pressure Intervention Trial (SPRINT) population. Methods Based on baseline albuminuria status (urine albumin/creatinine ratio [UACR], ≥30 or <30 mg/g) and the levels of estimated glomerular filtration rate ([eGFR], ≥60, 45–59, or <45 mL/min/1.73 m2), participants were classified into six subgroups to assess the risks associated with the primary outcome and mortality. The primary composite outcome was myocardial infarction, other acute coronary syndromes, stroke, heart failure, or mortality from cardiovascular causes. Results During a median follow-up of 3.26 years in 8,866 hypertensive patients, there were 352 deaths and 547 participants with the primary outcome. In adjusted Cox regression analysis using non-CKD and non-albuminuria (eGFR ≥60 mL/min/1.73 m2 combined with UACR <30 mg/g) as reference, albuminuria whether combined with CKD or not, showed significantly higher risk of both primary outcome and all-cause mortality in the total population. Whereas, non-albuminuria only combined with eGFR <45 mL/min/1.73 m2 showed significantly higher risk of both primary outcome and all-cause mortality in the intensive-therapy group. Discussion Non-albuminuric CKD did have higher risk of all-cause and CVD mortality only if the eGFR <45 mL/min/1.73 m2. Increased albuminuria conferred higher risk of primary outcome and all-cause mortality irrespective the levels of eGFR. Clinical trial registration ClinicalTrials.gov, number: NCT01206062.